Avaliação da soroprevalência aos alérgenos Der f 2 e Zen 1 do ácaro Dermatophagoides farinae em cães com dermatite atópica - Frezza, Ana Paula Di Martino [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
A dermatite atópica (DA) é uma doença crônica, inflamatória e pruriginosa da pele resultante da perda de barreira epidérmica, sensibilização e produção exacerbada de anticorpos IgE, direcionados, principalmente, contra alérgenos ambientais, mormente aos ácaros da poeira doméstica. Estudos com alérgenos dos ácaros da poeira doméstica são necessários para aprimoramento de testes sorológicos e intradérmicos e para confeccionar imunoterapia alérgeno específica com alta eficácia. O objetivo deste estudo foi avaliar a soroprevalência aos alérgenos Der f 2, Zen 1 e corpo do ácaro Dermatophagoides farinae em cães com DA do estado de São Paulo, Brasil. Foi utilizado o soro de 85 cães, os quais foram submetidos ao teste sorológico ELISA (Enzyme Linked Imunosorbent Assay) indireto para detecção de IgE alérgeno-específica para os alérgenos estudados. A soropositividade foi observada em 96% dos animais para Der f 2, 91% para Zen 1 e 96% para o corpo do ácaro. Devido à esta alta prevalência encontrada, sugerimos que Der f 2 e Zen 1 podem ser considerados alérgenos maiores para cães no estado de São Paulo.

Atopic dermatitis (AD) is a chronic, inflammatory and pruritic disease of the skin resulting from the loss of epidermal barrier, sensitization and exacerbated production of IgE antibodies, mainly directed against environmental allergens, especially to house dust mite. Studies with house dust mite allergens are required, aiming at the improvement of both serological and intradermal tests, in order to make specific allergen immunotherapy with high efficacy. The objective of this study was to evaluate the seroprevalence of Der f 2, Zen 1 and body of the Dermatophagoides farinae allergens in dogs with AD from the State of São Paulo, Brazil. Serum of 85 dogs were used, which were submitted to indirect enzyme-linked immunosorbent assay (ELISA) for the detection of allergen-specific IgE for the allergens studied. Serum of 85 dogs were used, which were using the indirect ELISA (Enzyme Linked Immunosorbent Assay) for the detection of allergen-specific IgE. Seropositivity was observed in 96% of the animals for Der f 2, 91% for Zen 1 and 96% for body of the mite. Due to this high prevalence, we suggest that Der f 2 and Zen 1 can be considered as major allergens dogs in the state of São Paulo.
Evaluation of seroprevalence to Der f 2 and Zen 1 allergens of the mite Dermatophagoides farinae in dogs with atopic dermatitis
Keywords: Alergia; ELISA; Dermatophagoides farinae; Canino; Soroprevalência; Allergy; ELISA; D. farinae; Canine; Soroprevalence